Is the destruction or removal of atmospheric methane a worthwhile option?. (24th January 2022) - Nisbet-Jones, Peter B. R.; Fernandez, Julianne M.; Fisher, Rebecca E.; France, James L.; Lowry, David; Waltham, David A.; Woolley Maisch, Ceres A.; Nisbet, Euan G.
Abstract : Removing methane from the air is possible, but do the costs outweigh the benefits? This note explores the question of whether removing methane from the atmosphere is justifiable. Destruction of methane by oxidation to CO2 eliminates 97% of the warming impact on a 100-yr time scale. Methane can be oxidized by a variety of methods including thermal or ultraviolet photocatalysis and various processes of physical, chemical or biological oxidizers. Each removal method has energy costs (with the risk of causing embedded CO2 emission that cancel the global warming gain), but in specific circumstances, including settings where air with high methane is habitually present, removal may be competitive with direct efforts to cut fugitive methane leaks. In all cases however, great care must be taken to ensure that the destruction has a net positive impact on the total global warming, and that the resources required would not be better used for stopping the methane from being emitted. This article is part of a discussion meeting issue 'Rising methane: is warming feeding warming? (part 2)'.